Determinants of Freight Forwarder Selection: A Decision-Making Model in Less-than-Container-Load (LCL) Shipping - Novita Widyaningrum; Edi Abdurachman; Juliater Simarmata; Tri Cahyadi; Rully Indrawan; Budi Mantoro; Christine Widilestari (Greenation Research & Yayasan Global Resarch National, 2026)
Previous studies in logistics and freight transportation have largely focused on service quality, customer satisfaction, or operational efficiency, but limited attention has been given to understanding how key service attributes influence customers’ behavioral intentions and final decisions in selecting freight forwarding services, particularly in the context of LCL shipping. This indicates a research gap in the existing literature on freight forwarding service selection. This study aims to develop a decision-making model for selecting freight forwarding services in Less-than-Container-Load (LCL) shipping by examining the influence of delivery time, price, and brand image on customers’ intention to use and decision to use freight forwarding services. A quantitative research approach was employed with data collected from 200 exporters and SMEs in Semarang, Surabaya, and Jakarta that utilize LCL shipping services. The data were analyzed using Structural Equation Modeling (SEM). The results indicate that delivery time, price, and brand image have significant positive effects on both intention to use and decision to use freight forwarding services. Among the independent variables, brand image shows the strongest influence on intention to use, while delivery time has the strongest impact on decision to use. Furthermore, intention to use significantly mediates the relationships between delivery time, price, brand image, and the decision to use freight forwarding services. This study contributes to the logistics and supply chain management literature by providing an integrated decision-making model for freight forwarding service selection in LCL shipping and offering practical insights for logistics providers to improve service strategies that enhance customer intention and decision to use their services.